The Carolina backcountry venture : tradition, capital, and circumstance in the development of Camden and the Wateree Valley, 1740-1810 - Lewis, Kenneth E. (The University of South Carolina Press, 2017)
"The Carolina backcountry venture is a historical, geographical, and archaeological investigation of the development of Camden, South Carolina, and the Wateree River Valley during the second half of the eighteenth century. The result of extensive field and archival work by author Kenneth E. Lewis, this publication examines the economic and social processes responsible for change and documents the importance of those individuals who played significant roles in determining the success of colonization and the form it took"--Provided by publisher.